Controle de qualidade e obtenção de extratos de espécies vegetais do cerrado brasileiro com potencial etnofarmacológico - Cardoso, Cássia Regina Primila; Salgado, Hérida Regina Nunes [UNESP]; Vilegas, Wagner [UNESP] (My University, 2013)
ANVISA (National Health Surveillance Agency) has published in recent years, laws that regulate the stages of the control of plants derivatives, including tests of macro and microscopic botanical identification, phytochemical determination, tests of authenticity and purity, microbiological testing, among other parameters. All the analytical procedures of plant drugs control required by law must be based on the Brazilian Pharmacopoeia, other Pharmacopoeias recognized by ANVISA or quality control guides of plant species published by the World Health Organization (WHO). This study aimed to evaluate some pharmacognostic, phytochemical screening and microbiological control of plant species of the Brazilian cerrado, which have indicated ethnopharmacological: Byrsonima intermedia (Bi), Bauhinia holophylla (Bh) and Myrcia bella (Mb). In addition, certain parameters were determined for obtaining extracts from plants sprayed and dried. These data are important to obtain new scientific information from Brazilian plants with therapeutic potential.
Keywords: Quality control; Herbal drugs; Microbiological assays; Brazilian cerrado; Pharmacopoeia